2020
DOI: 10.3847/1538-4357/ab96c4
|View full text |Cite
|
Sign up to set email alerts
|

Hunting Distant BL Lacertae Objects with the Photometric Technique Using Swift and SARA

Abstract: BL Lacertae objects represent a large fraction (22%) of γ-ray sources in the Third Fermi Large Area Telescope catalog (3FGL). Nearly half of the BL Lac object population remains without a redshift because of their featureless optical spectra. We aim to increase the number of BL Lac objects with a redshift measurement by using the photometric technique. For this work, we have used six Swift-UVOT filters and SDSS g′, r′, i′, and z′ optical filters mounted on the 0.65 m SARA–CTIO located in Chile and the 1.0 m SA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…One caveat of this method is that it works for sources with z > 1.3. This method has successfully found redshift estimates for 29 sources to-date (Kaur et al 2017a(Kaur et al , 2017bRajagopal et al 2020). We emphasize that our results are consistent with the updated 4FGL catalog classification as seen in Table 2, for the newly classified sources, which provides further evidence that our added classifications (not classified in the 4FGL) are likely robust.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…One caveat of this method is that it works for sources with z > 1.3. This method has successfully found redshift estimates for 29 sources to-date (Kaur et al 2017a(Kaur et al , 2017bRajagopal et al 2020). We emphasize that our results are consistent with the updated 4FGL catalog classification as seen in Table 2, for the newly classified sources, which provides further evidence that our added classifications (not classified in the 4FGL) are likely robust.…”
Section: Discussionsupporting
confidence: 85%
“…The observational evidence of finding FSRQs at typically higher redshifts than that of BL Lac objects suggests this scenario. However, several (29) BL Lac objects have been found at high redshifts (Rau et al 2012;Kaur et al 2017aKaur et al , 2017bRajagopal et al 2020). These blazar parameter spaces and the theories regarding their evolution need to be further explored by obtaining a more complete sample of both types of blazars.…”
Section: Introductionmentioning
confidence: 99%
“…We highlight in the plot both the objects studied in our spectroscopic campaign and the photometric campaign. The photometric dropout technique is based on the flux attenuation caused by the interaction of source photons by neutral Hydrogen and becomes particularly effective at z>1 (Rau et al 2012;Kaur et al 2017;Kaur et al 2018;Rajagopal et al 2020). It is clear that both campaigns resulted in several sources for which the HEPs are very near current estimates of the CGRH, as well The pink and green stars report the HEP for sources from the spectroscopic campaign, while the blue stars represent the HEP for sources from the photometric campaign (Rau et al 2012;Kaur et al 2017;Kaur et al 2018;Rajagopal et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The color of the circles represents the corresponding depth values as shown in the colorbar. The prediction from different EBL models: Finke et al 2010 (dotted green line), Domínguez et al 2011 (solid black line, with uncertainties shown as the shaded band), Gilmore et al 2012 (dashed red line), and Helgason & Kashlinsky 2012 (dotted-dashed blue line) are shown for comparison.The pink and green stars report the HEP for sources from the spectroscopic campaign, while the blue stars represent the HEP for sources from the photometric campaign(Rau et al 2012;Kaur et al 2017;Kaur et al 2018;Rajagopal et al 2020).…”
mentioning
confidence: 99%
“…As a result, out of the 2863 sources of the Fourth AGN Fermi-LAT catalog (4LAC, Ajello et al (2020)), only 1591 have redshift estimates, ranging from z = [0, 3], but mostly concentrate below z = 2. γ-Ray loud blazars with redshift estimates are relevant for our comprehension of the origin of the Extragalactic Background Light (EBL), which in turn let us probe the cosmic evolution of blazars (e.g., Singal et al (2012), Singal et al (2014), Singal (2015), Singal et al (2013a), Chiang et al (1995), Ackermann et al (2015), Singal et al (2013b) Marcotulli et al 2020), the intergalactic magnetic field (e.g., Venters & Pavlidou 2013), star formation rate history of our universe (e.g., Fermi-LAT Collaboration et al 2018), as well as constrain cosmological parameters (e.g., Domínguez et al 2019). The difficulty in spectroscopically measuring redshift in a significant fraction of BL Lacs and the importance of identifying high-z blazars has led to the development of photometric estimation techniques (photo-z, e.g., Kaur et al 2017Kaur et al , 2018Rajagopal et al 2020;Carrasco et al 2015;Krakowski et al 2016;Nakoneczny et al 2019 ). However, works using such methods typically produce redshift estimates for only ∼ 6 − 13% of their sample, making alternative methods necessary.…”
Section: Introductionmentioning
confidence: 99%